(untitled) (Al-Academy, 2026)
This research addresses the dialectic inherent in the concept of postmodernism and its impact on contemporary artists, particularly in the field of painting. It attempts to uncover and define this dialectic as an artistic and intellectual concept, ultimately aiming for a comprehensive and separate study of art schools and their influence by postmodern ideas. The research comprises four chapters. The first chapter is dedicated to the methodological framework, including the research problem, its significance and necessity, its scope, and the definition of terms. The second chapter presents the theoretical framework, comprising three sections: the first on the concept of dialectic, the second on the concept of postmodernism, and the third on artistic movements in the postmodern era. The third chapter covers the procedural framework, defining the research population and selecting the study sample. Twenty-four artworks were collected for analysis from the research population, from which four artworks by artists belonging to different art schools were selected. These four artworks were analyzed using a descriptive-analytical approach to determine the extent of dialectic in the works of postmodern artists. Finally, Chapter Four presents the research findings and conclusions, interpreting them in light of the objectives and relating them to the theoretical framework. Among the most important findings are the spontaneity and visual expression of emotions through color relationships and three-dimensional forms. This creates a kind of conflict within the artwork, presenting the viewer as a participant in the artistic process and projecting their own conflicts onto the artwork in a dialectical manner